Replication of nanoscale surface gratings via injection molding - Olga Muntada-López; Jordi Pina-Estany; Carles Colominas; Jordi Fraxedas; Francesc Pérez-Murano; Andres García-Granada (Micro and Nano Engineering, 2019)
Nanostructured gratings fabricated on silicon chips have been successfully transferred to polypropylene plastic parts by means of injection molding. Different sets of experiments were carried out along with a repeatability analysis in order to study the effect in the replication of process parameters such as maximum injection pressure, injection time, charge and polymer temperature, geometric factors such as width and separation between lines of the gratings and flow direction as well as demolding conditions. Among all factors, the one with a larger effect is the separation between consecutive trenches, which was studied in detail through Computational Fluid Dynamics simulations. In addition, a previously not reported sinking effect in the nanostructured area and a shrinking of the pattern period were characterized and simulated. Keywords: Plastic injection molding, Nanostructured surfaces, Computational fluid dynamics, Heat transfer